NAVIGATING RISK BY USING A MULTIFACETED APPROACH TO CONTINGENCY PLANNING FOR BLACK SMES IN SOUTH AFRICA'S AUTOMOTIVE INDUSTRY DURING COVID-19 - Peterson, Denis Desmond (Universitas Nusa Cendana, 2025)
This study examines contingencies used by Black-owned SMEs in South Africa’s automotive industry during the COVID-19 pandemic to manage risks during this period. Semi-structured interviews were conducted with 11 SMEs, comprising six micro-businesses and five small businesses located in Gauteng and the Eastern Cape. Thematic analysis was used to analyze the data, revealing the contingencies implemented as responses to mitigate the risks to their sustainability. The findings show that participants employed multifaceted contingency strategies across financial, operational, human resource, socioeconomic, and technological domains. These measures were both proactive and reactive, highlighting the adaptability and resilience of the SMEs. The study emphasizes the importance of targeted policies and frameworks to support these enterprises in navigating risks and ensuring sustainability. These insights are crucial for policymakers, business leaders, and stakeholders committed to fostering resilience in South Africa's small business sector. Keywords: Small Business; Contingencies, Covid-19; Automotive Industry